Application of The WEBUSE Method in Analyzing National Industrial Information Systems - Aliya Tasya, Nabilah; Dedi Irawan, Muhammad (Journal of Information Systems and Technology Research, 2023)
At this time the development of information systems is very rapid in various sectors. One of them is in the economic sector. Many information systems have sprung up in the economic sector, for example, the information system used by government agencies, namely the National Industrial Information System. The National Industrial Information System is an information system used by government staff to supervise data owned by each industrial company. This Information System has many features are home, industrial policies, e-reporting, helpdesk, and others. The application of an information system in an organization is inseparable from the user's perception of the information system. The Website Usability Evaluation (WEBUSE) method is an analytical method that allows users to assess the usability of the implemented web system. This method uses a questionnaire to obtain the required information. Therefore, this study uses the WEBUSE method in analyzing the National Industrial Information System to determine the value of the usability level of the system used. After doing the calculations, the results of the usability analysis of National Industrial Information System with the WEBUSE method get a point of 0.89 which includes an "Excellent" usability level. This usability level shows that the National Industrial Information System is following the wishes of its users.